2003
DOI: 10.1046/j.1439-0264.2003.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Study of Innervation and NADPH‐D Activity of the Thymus

Abstract: Acetylcholinesterase (ACHE)-positive nerve fibres in the thymus of the rat form perivascular plexuses as well as free ACHE-positive nerves, which do not follow the course of the vessels. A higher number of ACHE-positive nerves was observed in corticomedullary border and the medulla, a lower number in the cortex of the thymus lobuli. A gradual reduction of ACHE-positive intrathymus nerve formation was recorded and correlated with the increasing age of the rats. Nicotinamide adenine dinucleotide phosphate-diapho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…25 Our results are in agreement with other authors, who also confirmed that NADPH-d positive cells are present in the rat thymus. 26–28 The observation of the thymus after the application of retinoid acid confirms the resemblance of NADPH-positive cells described by Gulati et al 27 In a further study, the same authors studied these cells at the electron-microscopic level. 29 …”
Section: Discussionsupporting
confidence: 70%
“…25 Our results are in agreement with other authors, who also confirmed that NADPH-d positive cells are present in the rat thymus. 26–28 The observation of the thymus after the application of retinoid acid confirms the resemblance of NADPH-positive cells described by Gulati et al 27 In a further study, the same authors studied these cells at the electron-microscopic level. 29 …”
Section: Discussionsupporting
confidence: 70%
“…Although NO is less active in cells from normal mice ( 43 ), a spleen cell subpopulation produces enough NO during an in vitro immune response to completely prevent multiplication of T cells ( 44 , 45 ). Similarly, previous studies have demonstrated that a wide range of potential immunomodulatory functions may be expected for NO in the thymus, including the following: Induction of tolerance, restriction of major histocompatibility complex, lymphocyte trafficking and regulation of thymic endocrine output ( 33 , 36 , 37 , 42 ). Furthermore, if there are effects or changes in the cells due to BetA treatment, it is assumed that NO may be produced to perform its regulatory roles in the cells of these immune organs.…”
Section: Discussionmentioning
confidence: 71%
“…Although NADPH-d expression was detected after 4 days, a significant increase in expression was observed after 8 days of BetA treatment, indicating the contribution of NADPH-d in spleen NO generation during the entire treatment period. Similarly, a steady increase in NADPH-d activity in the thymus beginning from day 4 may specify an interactive outcome of NO on the thymus vascular and medulla regions, which may be involved in immune modulation ( 33 , 36 – 37 ). Although the function of NO in the thymus and spleen has not been demonstrated, the findings of the current study indicate that there is an association between the immunological effects induced by BetA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation